Analisis Big Five Personality Terhadap Keterlibatan Kerja Aparatur Sipil Negara (ASN) di Kota Manado - Hartati, Meike Endang (Peneliti.net, 2025)
This study aims to analyze the influence of the Big Five personality traits on work engagement among Civil Servants (ASN) in Manado City. The study used a quantitative approach with a descriptive survey design and cross-sectional method. The study sample consisted of 127 ASN selected using a non-probability sampling technique with a convenience sampling method. Data were collected through a Likert scale questionnaire to measure the five dimensions of the Big Five personality traits and work engagement. Data analysis was performed using simple linear regression with the help of SPSS 25 for Windows. The results showed that the dimensions of conscientiousness and neuroticism had a significant effect on ASN work engagement. In contrast, extraversion, agreeableness, and openness to experience did not show a significant effect. Overall, the contribution of personality to work engagement is relatively small, so other factors outside of personality are suspected to be more dominant in influencing ASN work engagement.